Green building material and technologies: assessing their potential in sustainable construction / Nor Azmi Bakhary - Bakhary, Nor Azmi (School of Civil Engineering, 2025)
The construction industry significantly impacts environmental factors through resource consumption and emissions. This paper examines green building materials and technologies to assess their suitability for sustainable construction, analyzing their environmental and economic benefits, as well as challenges to their advancement. Extensive literature on green building materials includes recycled steel, concrete, bamboo, and straw bales. The promotion of environmentally friendly technologies such as solar photovoltaic systems, geothermal heat pumps, and advanced HVAC systems is emphasized. This descriptive study relies on secondary research from scholarly journals, industry reports, and case studies, comparing the performance, advantages, and disadvantages of these materials and technologies. The study synthesizes findings to understand their potential in enhancing sustainable construction. The study reveals a strong correlation between sustainability and environmental impact concerning emissions, energy consumption, and water usage of green building materials. Economically, these materials are cost-efficient in the long term and increase property value, despite high initial costs. Challenges to adoption include high initial capital investment, lack of standardization, legal issues, and low market acceptance. Addressing these challenges is crucial for advancing sustainable practices. Comparing findings with existing literature supports the hypotheses related to the environmental and economic benefits of green building materials and technologies. However, concerns such as lack of supportive policies, absence of industry standardization, and general unawareness must be addressed to improve adoption rates. These challenges affect design approaches and highlight the need for science-based regulatory standards and continuous scientific advancements in sustainability. The findings suggest that sustainable building materials and technologies have the potential to revolutionize construction. Major outcomes include environmental benefits like reduced carbon emissions, enhanced water quality, and efficient resource management. Economic benefits include cost savings and revenue boosts. These results underline the significant impact sustainable materials and technologies can have on the future of construction, emphasizing the need for ongoing support and development in this field.